Numerical scattering simulations for estimating soot aggregate morphology from nephelometer scattering measurements. (January 2022) - Karlsson, Anders; Török, Sandra; Roth, Adrian; Bengtsson, Per-Erik
Abstract: Nephelometers are regularly used for air quality monitoring through scattering measurements of aerosols in the atmosphere. Less attention has been paid to the potential of estimating soot morphological parameters from nephelometer measurements in combination with scattering theory. In this work, we perform a fundamental laboratory study where an Ecotech Aurora 3000 nephelometer is used for measuring the scattering properties of soot with different characteristics. The nephelometer monitors the forward and backward scattering at three wavelengths (450 nm, 525 nm, and 635 nm) to retrieve information on the ratio of forward and backward scattering intensities, as well as the scattering wavelength dependence. An inverse scattering method, based on the Rayleigh–Debye–Gans theory, for determination of the equivalent fractal dimension ( D f ) and radius of gyration ( R g ) of soot particles from the experimental scattering data was developed. It is shown that the inverse method can estimate R g and D f when R g < 185 nm and from the wavelength dependence, information on the relative amount of organic soot could be obtained. For validation, estimated parameters are compared with the morphological parameters of soot sampled from the mini-CAST soot generator and evaluated using transmission electron microscopy (TEM). Uncertainties and limitations of the procedure are discussed. Highlights: A three-wavelength nephelometer measured forward and backward scattering of soot. R g and D f were estimated from nephelometer data using an inverse scattering method. RDG scattering simulations were applied to numerically constructed soot particles. Estimated R g and D f were compared with corresponding values from TEM analysis. The F ( m ( λ ) ) -ratio was estimated and related to the organic soot content.